Critical connections: The role of the built environment sector in delivering green cities and a green economy - Newton, P.; Newman, Peter (MDPI AG, 2015)
The green agenda for cities and the economy in general is a major focus of global institutions and is increasingly a major national and urban priority. Core issues and best practice for built environment businesses were collated from published studies and used in a survey of Australian firms to see how committed they were to the green economy. The results show high awareness of the challenges and opportunities with 85% of firms having sustainability as an established agenda with senior management and over 20% of built environment firms deriving more than 50% of their sales from green products and services. This is much higher in design firms and is globally high. Whilst recognizing the scope for more engagement by industry in transitioning to a low carbon green economy, there is doubt within the built environment sector about how to create a business case for innovative green ventures and a lack of certainty or encouragement from government about how to proceed.